Combining Ability and Heritability of Maize (Zea mays L.) Morphologic Traits under Water Stress and Non-stress at Flowering Stage - , A. M. M. Al-Naggar; , M. M. M. Atta (Archives of Current Research International, 2017)
The main objective of the present investigation was to estimate combining ability, genetic variance components and heritability of 12 morphologic traits of maize under water stress (WS) and well watering (WW) at flowering stage. Fifteen F1 genotypes of incomplete diallel crosses among 6 diverse inbred lines were evaluated under WS and WW at two seasons using a split plot design with three replications. The magnitude of general combining ability (GCA) was higher than specific combining ability (SCA) variance for all studied traits. The best general combiners for grain yield/plant (GYPP) (Sd-7 and IL-92) were also the best combiners for one or more yield traits, under WW and WS. The best cross in SCA effects for GYPP was IL171 × Sd7 followed by IL171 × IL17 under WS and IL24 × CML104 and IL171 × IL17 under WW. The magnitude of additive was much higher than dominance variance for all studied traits, except for ears/row (EPP) under WW and WS. Narrow-sense heritability (h2n) was generally of high magnitude (>60%) in most studied traits under both environments. Expected genetic advance (GA) from selection for studied traits in the two environments was generally of moderate magnitude (10-20%) for 11 out of 20 cases, namely plant height (PH), ear height (EH), leaf angle, kernels/row (KPR) and EPP, under WW and WS and GYPP under WS. The GA estimate for days to silking, rows/ear, KPP and 100-kernel weight under WW and WS and GYPP under WW, was of low magnitude (<10%). Under WS, heritability and expected genetic gain from selection were higher than WW for all studied traits, except PH and EH, where the opposite was true.